Oncological outcome audit of multivisceral resections for primary colorectal cancer: a single centre experience - Dimitrijevic, Ivan B; Barisic, Goran; Markovic, Velimir; Gavrilovic, Predrag; Bašić, Marica; Krivokapic, Zoran (Vojnosanitetski pregled, 2021)
Abstract Background/Aim. Colorectal cancer still presents a major health problem, with around 10% of patients in whom the tumor invades surrounding structures or organs. These patients are usually challenging even for an experienced colorectal surgical team. The decision for performing multivisceral resection (MVR) is often made intraoperatively, with no sufficient data on the tumor and patient condition. The percentage of perioperative morbidity and mortality is high and oncological outcome is often unfavorable.The aim of this study was to investigate the poor oncological outcome risk factors after MVR in the patients with colorectal carcinoma. Methods. This was a retrospective analysis of patients operated at the Department for Colorectal Surgery of the First Surgical Clinic, Clinical Centre of Serbia, Belgrade. The en bloc multivisceral resection for the primary adenocarcinoma of the colon and rectum was uniformly performed. Data were collected in prospectively designed database. Follow-up period was minimum 2 years. The patients were analyzed in terms of histopathological, demographical and follow-up data. Survival and time to recurrence were evaluated using the Kaplan–Meier method and the log-rank test. Results. Two hundred and thirteen patients were included in the study Their mean age was 59.9 ±12.0 years. The follow-up period was 33.8 ±29 months. Histopathology confirmed the true tumor infiltration of surrounding organ/structure in 126 (59.2%) patients. The R0 resection was confirmed in 173 (81.2%) patients. Five-year overall survival was 43.4%. Five-year survival for colon patients was 45.9% and in the rectal cancer group 40.9%. In the N0 group of patients, the overall survival in 5-year period was 66.7%. The N1 and N2 status proved the adverse effect on survival (overall 5-year survival 31.3% and 15.9%, respectively). The five-year local recurrence rate in the R0 group of patients was 17.7% and the percentage of distant metastases was 66.3%. Conclusion. The multivisceral resections are demanding procedures requiring a highly specialized surgical team and a high volume hospital. The oncological outcome of these procedures is still unfavorable. In the cases with the node positive disease, or the R1 resection, the perspective is poor. On the other hand, in the absence of these unfavorable factors, we can expect a good oncological outcome. More meticulous preoperative staging and aggressive preoperative treatment can further improve the results.